ChemInform Abstract: Synthesis of Pyridoacridines Through Anionic Cascade Ring Closure. Issue 49 (9th December 2014) - Petersen, Ida Nymann; Kristensen, Jesper Langgaard
Abstract A short synthetic strategy for the construction of pentacyclic heterocycles trough anionic cascade ring closure is developed.